ADAM10 sheddase activation is controlled by cell membrane asymmetry. (12th February 2019) - Bleibaum, Florian; Sommer, Anselm; Veit, Martin; Rabe, Björn; Andrä, Jörg; Kunzelmann, Karl; Nehls, Christian; Correa, Wilmar; Gutsmann, Thomas; Grötzinger, Joachim; Bhakdi, Sucharit; Reiss, Karina
Abstract: Dysregulation of the disintegrin-metalloproteinase ADAM10 may contribute to the development of diseases including tumorigenesis and Alzheimer's disease. The mechanisms underlying ADAM10 sheddase activation are incompletely understood. Here, we show that transient exposure of the negatively charged phospholipid phosphatidylserine (PS) is necessarily required. The soluble PS headgroup was found to act as competitive inhibitor of substrate cleavage. Overexpression of the Ca 2+ -dependent phospholipid scramblase Anoctamin-6 (ANO6) led to increased PS externalization and substrate release. Transfection with a constitutively active form of ANO6 resulted in maximum sheddase activity in the absence of any stimulus. Calcium-dependent ADAM10 activation could not be induced in lymphocytes of patients with Scott syndrome harbouring a missense mutation in ANO6. A putative PS-binding motif was identified in the conserved stalk region. Replacement of this motif resulted in strong reduction of sheddase activity. In conjunction with the recently described 3D structure of the ADAM10 extracellular domain, a model is advanced to explain how surface-exposed PS triggers ADAM10 sheddase function.